Efficacy and Safety of Tripterygium Wilfordii Hook. F for Connective Tissue Disease-Associated Interstitial Lung Disease:A Systematic Review and Meta-Analysis - Li, Yehui; Zhu, Wen; He, Hailang; Garov, Yordan Angelov; Bai, Le; Zhang, Li; Wang, Jing; Wang, Jinghai; Zhou, Xianmei (Frontiers in Pharmacology, 2021)
Background: Tripterygium wilfordii Hook. F (TwHF), a Chinese herbal medicine, has been proposed to treat CTD-ILD patient in China. Objectives: This systematic review and meta-analysis aimed to evaluate the efficacy and safety of TwHF for CTD-ILD. Methods: PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang, VIP, and CBM database were systematically searched up to November 2020. The randomized controlled trials (RCTs) comparing TwHF plus conventional therapy versus conventional therapy alone were included. We followed the PRISMA checklist in general, applying Cochrane handbook 5.1.0 and RevMan 5.3 to evaluate the quality of study and analysis the data. Results: Based on Cochrane handbook 5.1.0, 8 RCTs consisting 610 patients met the criteria and were selected for further analysis. The data demonstrates significant improvement in lung function with TwHF plus conventional treatment compared with conventional treatment (post-treatment FVC% [MD=8.68, 95%Cl (5.10, 12.26), P<0.00001], FEV1% [MD=11.24, 95%Cl (6.87, 15.61), P<0.00001], TLC% [MD=5.24, 95%Cl (0.30, 10.17), P=0.04] ). But no significant difference in the post-treatment DLCO% ( [MD=1.40, 95%Cl (-4.82, 7.61), P=0.66] ).Moreover, the data showed that TwHF combined with conventional treatment significantly reduced the HRCT integral of patients [MD=-0.65, 95% (-1.01, -0.30), P=0.0003] and the level of erythrocyte sedimentation rate (ESR) [MD=-9.52, 95%Cl (-11.55, -7.49), P<0.00001], c-reactive protein (CRP) [MD=-8.42, 95%Cl (-12.47, -4.38), P<0.0001], and rheumatoid factor (RF) [MD=-25.48, 95%Cl (-29.36, -21.60), P<0.00001].Compared to conventional therapy, the conventional therapy combined with TwHF significantly improved clinical effects [RR=1.34, 95%Cl (1.17, 1.53), P<0.0001], including four trials and 314 patients. In terms of improvement of symptoms and signs, the TwHF group showed a more significant improvement than conventional treatment (Cough [MD=-1.12, 95%Cl (-1.58, -0.66), P<0.00001], velcro rales [MD=-0.32, 95%Cl (-0.44, -0.20), P<0.00001], shortness of breath [MD=-1.11, 95%Cl (-1.67, -0.56), P<0.0001] ), but no statistical difference in the dyspnea [MD=-0.66, 95%Cl (-1.35, 0.03), P=0.06].There was no statistical significance in the incidence of adverse events. Conclusions: The meta-analysis indicated that TwHF combined with conventional treatment was more beneficial to patients in improving symptoms, lung function and laboratory indicators. As it’s small samples, the finding requires confirmation by further rigorously well-designed RCTs.